Management Accounting Information System: Case Study at the Kusan Hilir Pagatan District Office - Monika Handayani; Muhammad Bahit; Muhammad Najman (Universitas 17 Agustus 1945 Semarang, 2023)
Cash management is an important aspect of the financial management of a company or financial entity. Effective cash management can ensure the continuity of company operations, avoid financial problems, and help achieve set financial goals. This research aims to design a cash management information system at the downstream Kusan sub-district office. This research uses research and development methods for accounting information systems. The results of this research found that the accounting information system created at the downstream Kusan sub-district office can assist in producing reports of cash receipts and disbursements effectively and efficiently by cash management accounting.